Answer:
(3x^2 - 1)(3x^2 + 1)(9x^4 + 1).
Step-by-step explanation:
Using the identity for the difference of 2 squares;
a^2 - b^2 = (a - b)(a + b)
we put a^2 = 81x^8 and b^2 = 1 giving
a = 9x^4 and b = 1, so:
81x^8 − 1 = (9x^4 - 1)(9x^4 + 1)
Applying the difference of 2 squares to 9x^4 - 1:
= (3x^2 - 1)(3x^2 + 1)(9x^4 + 1).
Answer:7
Step-by-step explanation:
Answer:
The main parts of a proof are the statements and the reasons. The statements are things you want to prove, and the reasons are the justifications for the statements. Some parts of a proof will provide a given statement or a visual with some congruency
Step-by-step explanation:
Answer:
i think it is 51 degrees
Step-by-step explanation:
Answer:
-6x
Step-by-step explanation: